Overcoming the limitations of atomic-scale simulations on semiconductor catalysis with changing Fermi level and surface treatment - Ji, Seulgi; Jeon, Dong Won; Choi, Junghyun; Cho, Haneol; Park, Bo In; Roh, Ilpyo; Choi, Hyungil; Kim, Chansoo; Kim, Jung Kyu; Sim, Uk; Li, Danlei; Ko, Hyunseok; et al. (Journal of Materials Chemistry A, 2024)
Wide band gap metal oxide semiconductor catalysts mostly exhibit very huge variations of catalytic reaction activities and pathways depending on the preparation conditions, unlike metallic catalyst materials. Atomic-scale modeling and ab initio calculations are extremely challenging for metal oxide semiconductor catalysts because of two main reasons: (i) large discrepancies between computational predictions and experiments, (ii) typical cell size limitations in modeling for dilute level doping (<1020 cm−3) cocatalyst size-dependency (diameter >3 nm). In this study, as a new groundbreaking methodology, we used a combination of density functional theory (DFT) calculations and a newly derived analytical model to systematically investigate the mechanisms of catalytic methane (CH4) oxidation activity change of CeO2. The key hypothesis that the catalytic methane oxidation reaction can be followed by the Fermi level change in CeO2 was well demonstrated via comparison with our multi-scale simulation and several literature reports. Our new method was found to give predictions in the catalytic activity of wide band gap semiconductors for variations in defect concentrations and cocatalyst coverage with advanced efficiency and accuracy, overcoming the typical model size limitation and inaccuracy problems of DFT calculations.
Keywords: Atomic-scale simulations; Catalytic reactions; CeO 2; Co catalysts; Density-functional theory calculations; Metal oxide semiconductor; Reaction activity; Reaction pathways; Semiconductor catalysts; Wide-band-gap